Best practices for the safe use of parenteral nutrition multi-chamber bags - M. Sirvent; MV. Calvo; JC. Pérez-Pons; I. Rodríguez-Penín; E. Marti-Bonmatí; A. Vázquez; R. Romero; CL. Crespo; P. Tejada (Elsevier, 2014)
Patient security is one of the key aspects of the Health-System. Parenteral Nutrition is included in the ISMP's list of high-alert medication, being its appropiate use an essential element in maximizing effectiviness while minimizing the potential risk of errors associated with its use. Multi-chamber bags offer several advantages versus pharmacy bespoke bags. However, their apparent simplicity may induce to misuse, asuming their use requires limited consideration, thus increasing the risk of potential errors. For this reason, the Spanish Society of Hospital Pharmacist's Clinical Nutrition Group considered it essential to develop a list of safety practices regarding the use of parenteral nutrition multi-chamber bags. These recommendations are based on practices globally accepted to diminish errors in PN therapy